Analyzing the Impact of Time Management, Optimism, and Stress on Final-Year Student Success in Semarang - Mei, Mei Rahayu; Efriyani Sumastuti; Ratih Hesti Utami P (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study analyzes the influence of time management, social support, optimism, academic stress, and self-efficacy on the success of final-year students in Semarang. A total of 200 final-year students were surveyed using questionnaires, and the data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings reveal that optimism has a significant positive effect on student success, while time management, social support, academic stress, and self-efficacy do not significantly impact success. These results suggest that while optimism plays a key role in student achievement, the ability to manage time and cope with academic stress may not directly influence success. The study highlights the importance of fostering optimism among students to enhance their academic performance. Further research is recommended to explore additional factors that may contribute to student success in academic settings.